From trash to treasure: the role of bacterial extracellular vesicles in gut health and disease - Sun, Desen; Chen, Pan; Xi, Yang; Sheng, Jinghao (Frontiers in Immunology, 2023)
Bacterial extracellular vesicles (BEVs) have emerged as critical factors involved in gut health regulation, transcending their traditional roles as byproducts of bacterial metabolism. These vesicles function as cargo carriers and contribute to various aspects of intestinal homeostasis, including microbial balance, antimicrobial peptide secretion, physical barrier integrity, and immune system activation. Therefore, any imbalance in BEV production can cause several gut-related issues including intestinal infection, inflammatory bowel disease, metabolic dysregulation, and even cancer. BEVs derived from beneficial or commensal bacteria can act as potent immune regulators and have been implicated in maintaining gut health. They also show promise for future clinical applications in vaccine development and tumor immunotherapy. This review examines the multifaceted role of BEVs in gut health and disease, and also delves into future research directions and potential applications.